Enhanced AC133-specific CAR T cell therapy induces durable remissions in mice with metastatic small cell lung cancer. (1st November 2021) - Taromi, Sanaz; Firat, Elke; Simonis, Alexander; Braun, Lukas M.; Apostolova, Petya; Elze, Mirjam; Passlick, Bernward; Schumacher, Alicia; Lagies, Simon; Frey, Anna; Schmitt-Graeff, Annette; Burger, Meike; et al.
Abstract: Metastatic small cell lung cancer (SCLC) is not curable. While SCLC is initially sensitive to chemotherapy, remissions are short-lived. The relapse is induced by chemotherapy-selected tumor stem cells, which express the AC133 epitope of the CD133 stem cell marker. We studied the effectiveness of AC133-specific CAR T cells post-chemotherapy using human primary SCLC and an orthotopic xenograft mouse model. AC133-specific CAR T cells migrated to SCLC tumor lesions, reduced the tumor burden, and prolonged survival in a humanized orthotopic SCLC model, but were not able to entirely eliminate tumors. We identified CD73 and PD-L1 as immune-escape mechanisms and combined PD-1-inhibition and CD73-inhibition with CAR T cell treatment. This triple-immunotherapy induced cures in 25% of the mice, without signs of graft-versus-host disease or bone marrow failure. AC133 + cancer stem cells and PD-L1 + CD73 + myeloid cells were detectable in primary human SCLC tissues, suggesting that patients may benefit from the triple-immunotherapy. We conclude that the combination of AC133-specific CAR T cells, anti-PD-1-antibody and CD73-inhibitor specifically eliminates chemo-resistant tumor stem cells, overcomes SCLC-mediated T cell inhibition, and might induce long-term complete remission in an otherwise incurable disease. Highlights: AC133-specific CAR T cells eliminate cancer stem cells. Orthotopic SCLC mouse model reflects the clinical course of human metastatic SCLC. CD73 and PD-L1 expression drives immune-escape mechanisms in human primary SCLC. The triple-immunotherapy specifically eliminates chemo-resistant tumor stem cells. The triple-immunotherapy induced cures in 25% of the mice, without signs of GVHD.